An unnatural death by propan-1-ol and propan-2-ol - Skopp, Gisela; Gutmann, Isabelle; Schwarz, Clara-Sophie; Schmitt, Georg (International journal of legal medicine, 2015)
A fatality of an inpatient ingesting a disinfectant containing ethanol, propan-1-ol, and propan-2-ol is reported. The alleged survival time was about 1 h. Major findings at autopsy were an extended hemorrhagic lung edema, an edematous brain, and shock kidneys. Concentrations of alcohols and acetone, a major metabolite of propan-2-ol, were determined from body fluids (blood from the heart and the femoral vein, urine, gastric contents) and tissues (brain, muscle, liver, kidneys, lungs) by headspace/gas chromatography using 2-methylpropan-2-ol as the internal standard. All samples investigated were positive for propan-1-ol, propan-2-ol, ethanol, and acetone except stomach contents, where acetone was not detectable. The low concentration of acetone compared to propan-2-ol likely supports the short survival time. The concentration ratios estimated from the results are in accordance with the physico-chemical properties of the particular alcohols, their different affinities towards alcohol dehydrogenase as well as their interdependence during biotransformation. Autopsy did not reveal the cause of death. According to the few published data, blood concentrations of 1.44 and 1.70 mg/g of propan-2-ol and propan-1-ol, respectively, are considered sufficient to have caused the death. This case also points to the need to restrict access to antiseptic solutions containing alcohols in wards with patients at risk.